Implementation of Pancasila Student Profile in Elementary School Education with Project-Based Learning Approach - Dwi Utari; Achmad Ruslan Afendi (PT ARRUS Intelektual Indonesia, 2022)
This study aims to discuss in depth the implementation of the Pancasila student profile in elementary school education with a project-based learning approach. This study uses a literature review method with narrative analysis to deepen knowledge about the profile of Pancasila students and its implementation using a project-based learning model approach. The data collection technique used is by reviewing various articles that are relevant to the research topic. The findings are processed by data collection, and documentation and then analyzed and described descriptively. The results of this study show that the implementation of the Pancasila student profile in elementary school education with a project-based learning approach provides opportunities for students to learn in a fun situation, not stuck, having a flexible learning structure, learning activities that are more interactive and also directly involved with the environment. around to strengthen the various competencies that must be possessed by students in the Pancasila student profile. The Pancasila student profile strengthening project is designed so that students can investigate, solve problems and make decisions. Through this project, the cultivation and development of the character of mutual cooperation and creativity in students can be implemented. The use of project-based learning in this learning is also expected to be able to overcome the problems experienced by children including: 1) having low achievement; 2) having low memory; 3) paying less attention; 4) having a slower learning speed than other friends; 5) need more stimulation to do the task, and 6) experiencing problems of adaptation and social relations in the classroom.